High levels of flame retardants in vehicle dust indicate ongoing use of brominated and organophosphate flame retardants in vehicle interiors - Svobodová, Petra; Jílková, Simona Rozárka; Kohoutek, Jiří; Audy, Ondřej; Šenk, Petr; Melymuk, Lisa (Environmental monitoring and assessment, 2025)
Vehicles are unique indoor environments, with interiors dominated by plastic/synthetic materials and exposure to extremes of temperature and radiation, leading to substantial potential for emissions of plastic additives from vehicle materials and subsequent exposure to drivers and passengers. Flame retardants (FRs) and per- and polyfluoroalkyl substances (PFAS) were measured in 30 dust samples collected from dashboards, seats, and trunks of cars of the same make and model (year of manufacture 1996-2021) to evaluate levels in dust and time patterns in additive use across cars of different ages. PFAS were detected in all dust samples at low levels, while FRs were detected in all samples, with some compounds consistently exceeding µg/g levels, especially tris(1,3-dichloro-2-propyl) phosphate (TDCIPP) and decabromodiphenyl ether (BDE-209), substantially higher than in other indoor environments. Although cars were of the same model, large variations were observed in FR concentrations in dust between cars, emphasizing the challenge in generalizing FR exposures from vehicle dust. Concentrations of BDE-209 in vehicle dust did not decrease over the 1996-2021 period, suggesting that restrictions on DecaBDE have had limited impact, likely due to exemptions in regulations for the automotive industry. The high FR levels indicate ongoing use of both organophosphate and brominated FRs in vehicles on the European market, although flammability standards for interior car materials are not mandated by European regulations, and the continued presence of long-restricted FRs suggests the presence of recycled plastics in vehicles; this potential exposure source may be increasing as vehicle producers aim to improve material circularity.
Keywords: monitorování životního prostředí; Time trends; látky znečišťující vzduch; znečištění vzduchu ve vnitřním prostředí; Air Pollutants; Flame retardants; Cars; halogenované difenylethery; Environmental Monitoring; Automobiles; prach; PFAS; retardanty hoření; Air Pollution, Indoor; organofosfáty; automobily; Halogenated Diphenyl Ethers; Flame Retardants; Organophosphates; Dust exposure; Dust